2008
DOI: 10.2214/ajr.07.2710
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of High-Resolution CT in the Evaluation of Chronic Infiltrative Lung Disease in Children

Abstract: Our results showed there are limitations to diagnosing chronic infiltrative lung disease in children on the basis of CT data alone. We suppose that these differences are explained by the technical difficulties of high-resolution CT in children, the insufficient number of cases of and data on high-resolution CT of children, and the heterogeneity of lesions of a given cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 38 publications
2
18
0
1
Order By: Relevance
“…The observations described here derive from two observational studies that found that CT scanning is more likely than CXR to accurately identify DLD in children (17,35), numerous case series that reported a strong correlation between histologic findings and the thin-section CT scan appearance in children with surfactant protein C mutation (42), neuroendocrine cell hyperplasia of infancy (NEHI) ( Figure 5) (20) and other DLDs (17,19,35), and two studies that demonstrated that CT scanning is superior to MRI in resolution and in identifying ground glass opacity, normal peripheral bronchi, and air trapping in patients with cystic fibrosis (43,44). Although cystic fibrosis is not a chILD disorder, resolution is an important determinant of image quality, and the findings of air trapping and ground glass opacity are key observations in chILD.…”
Section: Diagnostic Testsmentioning
confidence: 97%
See 1 more Smart Citation
“…The observations described here derive from two observational studies that found that CT scanning is more likely than CXR to accurately identify DLD in children (17,35), numerous case series that reported a strong correlation between histologic findings and the thin-section CT scan appearance in children with surfactant protein C mutation (42), neuroendocrine cell hyperplasia of infancy (NEHI) ( Figure 5) (20) and other DLDs (17,19,35), and two studies that demonstrated that CT scanning is superior to MRI in resolution and in identifying ground glass opacity, normal peripheral bronchi, and air trapping in patients with cystic fibrosis (43,44). Although cystic fibrosis is not a chILD disorder, resolution is an important determinant of image quality, and the findings of air trapping and ground glass opacity are key observations in chILD.…”
Section: Diagnostic Testsmentioning
confidence: 97%
“…The observation that diagnostic testing provides a specific diagnosis for more than 50% of patients suspected of having ILD derives from three multicenter retrospective studies (6,11,15) and two single-center prospective case series (13,16) that described the occurrence of ILDs and DLDs in children and the utility of diagnostic testing, as well as four diagnostic accuracy studies for high-resolution CT (HRCT) in DLDs (17)(18)(19)(20). Our confidence in the results of these studies is diminished by the study design, the absence of studies using the current chILD syndrome definition in a general pediatric pulmonary patient population, and the small numbers of patients with some forms of DLD, particularly the more recently recognized entities.…”
Section: Definitionsmentioning
confidence: 99%
“…Vrielynck et al evaluated the accuracy of chest CT in the differential diagnosis of chronic infiltrative lung disease in children. Among a cohort of 59 patients with nine disorders, PAP was the most frequently properly diagnosed (72%), showing that the HRCT appearance of PAP is suggestive of the disease [8]. Current guidelines imply, that characteristic image of HRCT together with a typical results of the examination of BAL are sufficient criteria for establishing diagnosis, without histological confirmation [2,7].…”
Section: Discussionmentioning
confidence: 99%
“…Las lesiones radiológicas nos permiten clasifi car, pronosticar e iniciar un tratamiento en los pacientes (tabla 3) 1,4 ; siendo la TACAR la herramienta más valiosa para el diagnóstico. Las imágenes tomográfi cas más observadas por Vrielynck y col fueron el vidrio esmerilado, engrosamiento septal, adenopatías bilaterales, engrosamientos intercisurales y las bandas parenquimatosas no septales 4,12 . La biopsia transbronquial (BTB) es el procedimiento más recomendado para el diagnóstico de la sarcoidosis pulmonar, aunque se pueden realizar biopsias en piel, hígado y glán-dulas salivales, la BTB es positiva en el 90% de los casos con adenopatías radiológicamen-te visibles, la biopsia pulmonar está indicada cuando los sitios para biopsiar son inaccesibles y la radiografía y/o TACAR son anormales 4 .…”
Section: Discussionunclassified